PERFORMANCE OF PHOTOCATALYST BASED CARBON NANODOTS FROM WASTE FRYING OIL IN WATER PURIFICATION (Universitas Negeri Semarang, 2016)
Carbon Nanodots (C-Dots) from waste frying oil could be used as a photocatalyst in water purification with solar light irradiation. Performance of C-Dots as a photocatalyst was tested in the process of water purification with a given synthetic sewage methylene blue. The tested was also conducted by comparing the performance C-Dots made from frying oil, waste fryng oil as a photocatalyst and solution of methylene blue without photocatalyst C-Dots. Performance of C-Dots from waste frying oil were estimated by the results of absorbance spectrum. The results of measurement absorbance spectrum from the process of water purification with photocatalyst C-Dots showed that the highest intensity at a wavelength 664 nm of methylene blue decreased. The test results showed that the performance of photocatalyst C- Dots from waste frying oil was better in water purification. This estimated that number of particles C-dots is more in waste frying oil because have experieced repeated the heating process so that the higher particles concentration make the photocatalyst process more effective. The observation of the performance C-Dots from waste frying oil as a photocatalyst in the water purification processes become important invention for solving the problems of waste and water purification.